SCIENTIFIC IDEAS ABOUT COMPLEX SYSTEMS (Scientific journal of the Fergana State University, 2023)
Nowadays the humankind deals with the complex open systems, regarding the society and the changes taking place in it belong to a complex system. A complex system consists of complex elements. Complex systems are researched by synergetic ideas, terms and methods. In the given article, problems, such as, a term of system, and its meaning, its differences from the object used in the classical science, becoming wholeness by inter-influence of elements and inter-connection of them are philosophically analysed